A new genus and four new species of the scale insect family Eriococcidae (Hemiptera: Coccoidea) from the Austro-Oriental Region - Kozár, Ferenc; Williams, Douglas J.; Benedicty, Zsuzsanna Konczné (Zootaxa, 2009)
A new genus, Hoyicoccus Williams & Kozár gen. n., and two new species, Hoyicoccus hendersonae Kozár & Williams and Eriococcus szentivanyi Kozár & Williams are described from Sabah, Malaysia. In addition, the genus Sangicoccus Reyne is discussed: Sangicoccus truncatispinus (Reyne) is redescribed and two new species, namely Sangicoccus morrisoni Kozár & Konczné Benedicty and Sangicoccus reynei Kozár & Konczné Benedicty, are described. Sangicoccus is now known off palms from Irian Jaya and Sulawesi in Indonesia, and from the Philippines and Papua New Guinea. A key is provided for the separation of the known species of Sangicoccus.